Analisis Faktor-Faktor yang Mempengaruhi Penerimaan Masyarakat terhadap Produk Perbankan Syariah - Ashilah Razaktania Widodo; Fauzatul Laily Nisa (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Most of the population in Indonesia is Muslim, this is a large market area for Islamic banks. With the existence of Islamic banks that offer services similar to Islamic sharia or based on the Qur'an, this makes the Muslim community interested in the products offered by Islamic banks. This product is something that can be provided to the market to generate attention, bought, used, or consumed that is able to satisfy a desire or need. By prioritizing very attractive services and facilities, it can also attract customers to use products or goods provided by Islamic banks. Islamic banks must be more active in communicating with their customers, especially if they have competitors.